Auricular reconstruction for microtia: A review of available methods. Issue 1 (March 2014) - Baluch, Narges; Nagata, Satoru; Park, Chul; Wilkes, Gordon H; Reinisch, John; Kasrai, Leila; Fisher, David
Several surgical techniques have been described for auricular reconstruction. Autologous reconstruction using costal cartilage is the most widely accepted technique of microtia repair. However, other techniques have certain indications and should be discussed with patients and families when planning for an auricular reconstruction. In the present review, the authors discuss the main surgical techniques for auricular reconstruction including autologous costal cartilage graft, Medpor (Stryker, USA) implant and prosthetic reconstruction. To further elaborate on the advantages and disadvantages of each technique, the authors invited leaders in this field, Dr Nagata, Dr Park, Dr Reinisch and Dr Wilkes, to comment on their own technique and provide examples of their methods.